THE RELATIONSHIP BETWEEN JOB SATISFACTION AND WORK ENVIRONMENT WITH EMPLOYEE WORK SPIRIT AT THE JAKARTA COOPERATIVE AND UMKM SERVICE - Mega Wiliandani; Chon Cho Reynols Manday (Journal of Golden Generation Economic, 2025)
This study was conducted to analyze the influence of job satisfaction and work climate on employee morale at the Jakarta City Cooperatives and SMEs Office. The method used in this study was a sampling method, with 35 respondents taken from the relevant population. Based on the results of the F test, the F count value was 14.405 which was greater than the F table of 3.285, with a significance of 0.000 which was smaller than the significance level of 0.05. This indicates that the null hypothesis (H0) is rejected and the alternative hypothesis (H1) is accepted, which means that job satisfaction and work climate simultaneously have a significant effect on employee morale. From the results of the t test, it is known that the t count value for job satisfaction is 3.181, greater than the t table of 1.692, with a significance level of 0.003 <0.05, which indicates a significant effect on work morale. Meanwhile, the work climate variable also showed a significant influence, with a calculated t value of 4.363 > t table 1.692 and a significance level of 0.000. The Adjusted R Square value of 0.441 indicates that 44.1% of the variation in work morale can be explained by the job satisfaction and work climate variables. The remaining 55.9% is influenced by other factors outside this research model.